Mycobacterial Cell Wall Stimulant in the Treatment of Squamous Cell Carcinoma: A Case Series Regarding Treatment in Equine, Bovine and Caprine Patients - Halleran, Jennifer; Yau, Katie; Paegelow, Jillian; Streeter, Robert; Foster, Derek (Frontiers in Veterinary Science, 2021)
Squamous cell carcinoma (SCC) is a common dermatological neoplasia found in large animal species. Treatment options, such as surgery and cryotherapy may be difficult or not feasible. Alternative therapies, such as immunomodulating drugs, can potentially be used for companion large animals. The hypothesis of the following retrospective study is: following multiple intravenous and intralesional injections of a mycobacterial cell wall stimulant (MCW) regression of SCC in equine, bovine and caprine patients will be observed. In this retrospective case series, patients included are 2 bovine, 2 caprine and 3 equine patients. The medical records at two different teaching veterinary hospitals were searched for cases with a positive histopathological diagnosis of squamous cell carcinoma that were subsequently treated with MCW, as either the sole therapy, or in conjunction with other therapies. Seven cases were included in this retrospective study. The median duration of therapy was 56.5 days, with 3 of the 7 patients being euthanized. Significant complications were seen in 3/7 patients. Repeated injections of a MCW may lead to reduction in lesion size of SCC in some cases, but long-term resolution is unlikely and the risk of significant complications is high.